(untitled) (Heritage, 2024)
Religion teaches about the soul as the essence of human being, but modern neuroscience and physics are getting closer to this concept in their research. The soul is immortal by grace. From the Orthodox Christian point of view, the highest level of development of the human soul is the discovery and direction of the soul towards God. At the base of all physics lies the principle of action from which all the basic laws of physics are derived, and the utmost form of this principle would correspond to biological behavior. Living organisms would behave as a consequence of causally determined quantum processes. The Penrose-Hameroff model considers the "soul" as a quantum computer that exists in the material world while the human individual is alive, but after biological death continues life in the fine quantum structure of the created world. The process of decoherence, which occurs when a quantum object comes into contact with the environment, takes part in the suppression of quantum effects on the macroplane. The Penrose-Hameroff model assumes that tubulins are the quantum units in microtubule quantum computers. Derandomization (in the sense of order), as opposed to entropy (in the sense of disorder) is an essential prerequisite of life. Derandomization (orderliness) is enabled by enformy. The necessity of introducing a "third" basic principle into the theory of "everything" reflects the unsustainability of an exclusively materialistic approach. They could say that both science and religion talk about the same phenomena, known in different ways, with different terminology but the same essence.